The Effect of Ratio of Passion Fruit with Star Fruit Juice and Concentration of Arabic Gum on Quality of Jelly Candy - Defi T. Simbolon; Zulkifli Lubis; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to determine the effect of passion fruit with star fruit juice and concentration of arabic gum on the quality of jelly candy. This research was using factorial Completely Randomized Design (CRD) with two factors, i.e: ratio of passion fruit with star fruit juice (S) : (70%:30% ; 60%:40% ; 50%: 50%; 40%:60%) and concentration of arabic gum (A): (0,5%, 1,0%, 1,5%, and 2,0%). The analyzed parameters were water content (%), ash content (%), vitamin C content (mg/100 g sample), total soluble solid (ºBrix), total acid (%),and organoleptic values (colour, taste, texture, and aroma).The results showed that the ratio of passion fruit and star fruit juice had highly significant effect on water content, vitamin C content, total soluble solid, total acid, score of organoleptic values of taste and texture. Arabic gum concentration had highly significant effect on moisture content, ash content, and vitamin C content and has significant efect on score of organoleptic values of texture. Interactions of the two factors had highly significant effect on moisture content. The best treatment which gave the best effect on jelly candy was 70%:30% of passion fruit and star fruit juice and 2,0% arabic gum. Keywords: arabic gum, jelly candy, passion fruit, star fruit.